ORGANIZATIONAL CULTURAL EVALUATION: A CASE STUDY OF AN ACQUIRED COMPANY IN HONG KONG UNDER MERGER AND ACQUISITION ENVIRONMENT - SHU CHUNG LO, RONNY (Global journal of Business and Integral Security, 2021)
This study presents some findings that may contribute to the academic and practical fields on a topic of organizational culture evaluation under a merger and acquisition (M&A) environment in Asian context. Zueva-Owens, Fotaki & Ghauri’s (2012) work is the inspiration and theoretical foundation of this study, and the research is based on a real acquisition case in Hong Kong. In order to gain an in-depth understanding and insight of the underlying reasons and discussions for an interest study topic, a qualitative research method with individual interviews and questionnaires involving the acquired company’s members is adopted in this study. The contribution of the study is not aimed to come up with a new theory, but to further explore and support the findings of Zueva-Owens et al., (2012), and extend their studies by empirically demonstrating that the same cultural evaluation process can be found in the context of Asian companies. Thus, the acquired company’s members do change their evaluation on the acquirer’s norms and values across different postacquisition integration stages. Furthermore, the study also contributes on organizational culture aspects by showing some interesting findings that the acquired company’s members choose to “refuse” the norms and values of the acquirer under different context of economic environment, company financial status and corporate cultures. The findings of the study have important implications for managers wishing to guide post-acquisition integration for the merging companies with Asian context. The results, discussions and recommendations may be used as a reference for those corporations which are actively looking for M&A’s opportunities in Hong Kong. Besides, for those newly acquired and acquiring companies, their executives may also make use of the findings for refining the integration process particularly on the aspects of human capital and cultural alignment among themselves